Six new Brazilian species of Polana (Varpulana) (Hemiptera: Cicadellidae: Gyponini) with key to males - Domahovski, Alexandre Cruz; Cavichioli, Rodney Ramiro (Zootaxa, 2017)
Six new species of Polana (Varpulana) are described and illustrated, all from Brazil: P. (V.) bahiensis sp. nov., state of Bahia; P. (V.) grossii sp. nov., states of Bahia and Minas Gerais; P. (V.) intricata sp. nov., state of Bahia, P. (V.) naja sp. nov., states of Bahia and Minas Gerais; P. (V.) sapitanduva sp. nov., states of Paraná and Rio de Janeiro and P. (V.) vulgaris sp. nov., state of Paraná. A key to 11 known species of P. (Varpulana) is presented. New records from several Brazilian states are added.